2019
DOI: 10.1017/s1047951119002919
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adverse events within one year after atrial septal closure in children: a retrospective follow-up study

Abstract: Introduction:Secundum atrial septal defect is one of the most common congenital heart defects. Previous paediatric studies have mainly addressed echocardiographic and few clinical factors among children associated with adverse events. The aim of this study was to identify neonatal and other clinical risk factors associated with adverse events up to one year after closure of atrial septal defect.Methods:This retrospective case–control study includes children born in Sweden between 2000 and 2014 that were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The incidence of postoperative complications in symptomatic patients in our study was low [19] and comparable with reports in older asymptomatic patients [18,21,22]. Tanghoj et al studied risk factors for adverse events following transcatheter and surgical ASD closure in children born preterm and concluded that prematurity was not a risk factor for post-procedural complications despite earlier procedural age, larger ASD size, and higher comorbidity than term infants [23,24].…”
Section: Hemodynamic Improvement Granted By Asd Closuresupporting
confidence: 85%
“…The incidence of postoperative complications in symptomatic patients in our study was low [19] and comparable with reports in older asymptomatic patients [18,21,22]. Tanghoj et al studied risk factors for adverse events following transcatheter and surgical ASD closure in children born preterm and concluded that prematurity was not a risk factor for post-procedural complications despite earlier procedural age, larger ASD size, and higher comorbidity than term infants [23,24].…”
Section: Hemodynamic Improvement Granted By Asd Closuresupporting
confidence: 85%
“…Second, we could not compare ASD for different criteria and we had no precise data about the diameter of ASD. Children with symptomatic ASD have higher morbidity than those with no symptoms, so future studies should provide further analysis by risk of ASD [36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed rates of ASD and CHD in the study might be overestimated than most previous studies [15,16,28]. A retrospective case-control study in Sweden including children under 18 years old, showed that only symptomatic ASD were associated adverse outcomes [38]. We should perform further analysis according to the risks of ASD in future.…”
Section: Patients' Characteristics and Risk Factors For Chdmentioning
confidence: 76%